National Strategy Midterm Review (Academic Journal of Internal Affairs, 2022)
Aim: Hungary has stepped up its efforts to fight against trafficking in human beings, the modern slavery in recent years. The national strategy for 2020‒2023 laid down the frameworks in which priority areas include the awareness-raising of vulnerable groups, the support services for identified victims and the efficiency of of law enforcement.Methodology: The strategy is made up of two-year action plans for 2020‒2021 and subsequently for 2022‒2023.Findings: The present study elaborates on the policy directions and main results in the field of counter-trafficking as well as the key actions to be taken in the coming years.Value: The division of strategic planning enables us to carry out a midterm evaluation and set the future goals in light of the experience to date.
Keywords: trafficking in human beings; exploitation; strategy; action plan